ENHANCING STUDENTS’ WRITING ACHIEVEMENT, CRITICAL THINKING, AND SELF EFFICACY THROUGH PROJECT BASED LEARNING (PBL) IN STATE ISLAMIC INSTITUTE OF CURUP - Suhermanto, Hadi; Edy, Sarwo; Apriani, Eka; Esmianti, Farida; Wijayanti, Erfin; Muthmainnah, Muthmainnah; Durgayan, Alesa (English Community Journal, 2024)
The purpose of this study is to find out how project-based learning may help students become more proficient writers, critical thinkers, and self-sufficient. The descriptive-quantitative method was used in this study. This approach focused on combining numerical data. Using a whole sample approach, the study focuses on sixty students enrolled in the Institute for Islamic Studies of Curup's English Study Programme. The study examined how students' writing proficiency, critical thinking, and self-efficacy in English—their target language—were affected by project-based learning (PBL). With a 14.46-point gain between the pre- and post-test writing achievement, the findings demonstrated a considerable improvement. The critical thinking essay writing score of fifth-semester students rose from 78.43 to 84.05, representing a 04.02 point gain from the start of the exam. Five categories of analysis were applied to the data: organisation, focus, reasoning, integrations, and conventions. According to the study's findings, PBL raised students' self-efficacy in writing classes.